Pelatihan Kader Kelas Ibu Hamil “Persiapan 1000 Hari Pertama Kehidupan” Di Desa Leminggir Kecamatan Mojosari Kabupaten Mojokerto - Heni Purwati; Etik Khusniyati; Elies Meilinawati; Faisal Ibnu (Universitas Jenderal Achmad Yani Yogyakarta, 2020)
The first 1000 days of life (HPK) are the most important part of human life. At this time parents have an important role to provide quality care and care in accordance with the stage of child development, because at this time the child's growth and development process begins. nutrition for this group must be seen as part of an investment to reduce poverty through improved education and health. The existence of new information about something will provide a new cognitive basis for the formation of a person's attitude. Audiovisual makes a huge contribution in changing people's behavior, especially in the aspects of information and persuasion. This community service activity is carried out by giving cadre health education given a pre-test questionnaire to measure the cadre's knowledge then health education is conducted after it is given a post test. Knowledge score before the treatment was obtained an average of 81.0909 and after treatment increased to 85.2727 where the score contained a difference of 4.1818 or an increase of 45.4%, a score of ρ-value = 0.016 (ρ-value <0, 05) which means there is a significant difference in scores between before and after health education using audio-visual media (video) for cadres of pregnant women or there is a significant increase in knowledge about the preparation of the First 1000 Days of Life after health education using audio-visual media ( rich media)